Science and technology dimensions of the SIDS programme of action - St. Aimee, Donatus (UN. ECLAC/CDCC Port of SpainTT, 1995)
Focuses on the critical role of technology in the development process and some of the mechanisms that can be put in place for technological information sharing given the limited research and development resource base of the region.